Memória e etnicidade da comunidade quilombola do ramal do Piratuba no município de Abaetetuba/Pa - SANTOS, Nice Cardoso dos (2024)
This research seeks to understand the historical process and is justified by the importance of knowing the origins and formation of the Quilombo community Extension of Piratuba in Abaetetuba, and tries to point out some evidence to reveal the perceptions of residents regarding memory and ethnicity of the community. By analyzing experiences of the social group it appears that the memory that gives meaning to your story. Although much has been written about the history of blacks in Brazil, the changes occurring in Brazilian society especially after the promulgation of the 1988 Constitution.'s Arrival black men and women took to the country as a result of the perverse process of enslavement. This study is an identification of memory, culture maroon remainder of this community, which is in the municipality of Abaetetuba countryside.